Dynamic Implant Surgery-An Accurate Alternative to Stereolithographic Guides-Systematic Review and Meta-Analysis - Jordi Marques-Guasch; Anna Bofarull-Ballús; Maria Giralt-Hernando; Federico Hernández-Alfaro; Jordi Gargallo-Albiol (MDPI AG, 2023)
(1) Background: Dynamic guided surgery is a computer-guided freehand technology that allows highly accurate procedures to be carried out in real time through motion-tracking instruments. The aim of this research was to compare the accuracy between dynamic guided surgery (DGS) and alternative implant guidance methods, namely, static guided surgery (SGS) and freehand (FH). (2) Methods: Searches were conducted in the Cochrane and Medline databases to identify randomized controlled clinical trials (RCTs) and prospective and retrospective case series and to answer the following focused question: "What implant guidance tool is more accurate and secure with regard to implant placement surgery?" The implant deviation coefficient was calculated for four different parameters: coronal and apical horizontal, angular, and vertical deviations. Statistical significance was set at a p-value of 0.05 following application of the eligibility criteria. (3) Results: Twenty-five publications were included in this systematic review. The results show a non-significant weighted mean difference (WMD) between the DGS and the SGS in all of the assessed parameters: coronal (n = 4 WMD = 0.02 mm; p = 0.903), angular (n = 4 WMD = −0.62°; p = 0.085), and apical (n = 3 WMD = 0.08 mm; p = 0.401). In terms of vertical deviation, not enough data were available for a meta-analysis. However, no significant differences were found among the techniques (p = 0.820). The WMD between DGS and FH demonstrated significant differences favoring DGS in three parameters as follows: coronal (n = 3 WMD = −0.66 mm; p =< 0.001), angular (n = 3 WMD = −3.52°; p < 0.001), and apical (n = 2 WMD = −0.73 mm; p =< 0.001). No WMD was observed regarding the vertical deviation analysis, but significant differences were seen among the different techniques (p = 0.038). (4) Conclusions: DGS is a valid alternative treatment achieving similar accuracy to SGS. DGS is also more accurate, secure, and precise than the FH method when transferring the presurgical virtual implant plan to the patient.